Enhancing Durability of Multi-Cavity Forging Tools through Process Automation - Meller, Artur; Legutko, Stanislaw; Mroz, Adrian; Piechowski, Mariusz; Kedziora, Hubert; Cernohlavek, Vit (Manufacturing Technology Journal, 2024)
The article highlights the promising potential of automating the forging process to enhance the durability of multi-cavity forging tools. Entrepreneurs aim to boost production efficiency by increasing output per unit of time and reducing the degradation of forging dies and punches. The high costs associated with specialized materials and complex manufacturing processes for these tools elevate the final product price. Automation offers a viable alternative, ensuring consistent process parameters and reducing the physical strain on workers. This consistency leads to extended tool durability, even without the use of special manufacturing techniques for their production. The study simulates the durability of multi-cavity dies in automated operations, demonstrating substantial advantages compared to manual forging. Simulation programs for forging processes and tool durability offer significant cost savings by providing insights into potential fatigue cracks, aiding in decision-making, and verifying operational parameters and tool designs. These simulations reduce the need for extensive: real-world tests and modifications of the forging tools.
Keywords: Die forging; Forging simulation; Forging dies durability; Material fatigue; Multi-cavity dies